Dosimetric Comparison between Volumetric Modulated Arc Therapy (VMAT) and Intensity-Modulated Radiotherapy (IMRT) for Dental Structures of Head and Neck Cancer Patients. (5th April 2022) - Ma, Yan; Zhou, Jianfeng; Wang, Hongyong
Abstract : Background . This retrospective study aimed to evaluate the radiation dose delivered to dental structures in intensity-modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) without dental dose constraints, compare the dosimetry differences of dental structures between the two radiation techniques, and determine whether dental structures should be one of the organs at risk for IMRT and VMAT plans according to the dosimetric analysis. Materials and Methods . A total of 138 head and neck cancer patients (nasopharyngeal, oral cavity, pharyngeal, hypopharynx, and larynx), who underwent IMRT (69 patients) or VMAT (69 patients) from March 2016 to March 2021 in our hospital, were included to assess the dosimetry difference between two radiotherapy techniques for dental structures. Results . The radiation dose delivered by IMRT and the mean maximum doses delivered by VMAT to the maxillary teeth of nasopharyngeal cancer patients were significantly higher than the dose received by the mandibular teeth. In contrast, the mandibular teeth of oral cavity cancer, oropharynx cancer, and laryngeal cancer received higher radiation doses than maxillary teeth. Except for mandibular teeth of oral cancer patients, the molars received significantly high-dose radiation than premolars and/or incisors in both radiotherapy techniques. No significant difference was observed between IMRT and VMAT in the dosimetric comparison of dental structures, except that oral cavity cancer patients treated with VMAT received a significantly higher mean average dose than those treated with IMRT. When PTV included level Ib, the radiation doses of the mandibular teeth delivered by both radiotherapy techniques were significantly higher than that in PTV when level Ib was excluded. Conclusion . Without dental dose constraints, no major difference was observed between IMRT and VMAT plans in tooth dose distribution. We suggest that dental structures should be delineated as part of the organ at risk (OAR) when IMRT and VMAT are planned. Meanwhile, attention should be paid to dental structures that might have a high-dose area according to the specific tumor location.